2022
DOI: 10.3389/fmicb.2022.833790
|View full text |Cite
|
Sign up to set email alerts
|

Metatranscriptomic Analysis of the Chicken Gut Resistome Response to In-Feed Antibiotics and Natural Feed Additives

Abstract: The emergence of resistance against common antibiotics in the gut microbiota is a major issue for both human and livestock health. This highlights the need for understanding the impact of such application on the reservoir of antibiotic resistance genes in poultry gut and devising means to circumvent the potential resistome expansion. Phytogenic feed additives (PFAs) are potential natural alternative to antibiotic to improve animal health and performance, supposedly via positively affecting the gut microbial ec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 77 publications
0
7
0
Order By: Relevance
“…bation of gut flora homeostasis compared to conventional antibiotic treatments (Hassan et al 2020). SCE belongs to the phenolic PFA group and has a higher antioxidant capacity due to its high phenolic content (Koorakula et al 2022). In this study, the daily feed intake and daily gain of piglets supplemented with SCE did not differ from those of the control group, even though SCE contains more crude protein and fat, which indicated that SCE did not affect the appetite and growth rate of piglets after weaning.…”
Section: Discussionmentioning
confidence: 51%
“…bation of gut flora homeostasis compared to conventional antibiotic treatments (Hassan et al 2020). SCE belongs to the phenolic PFA group and has a higher antioxidant capacity due to its high phenolic content (Koorakula et al 2022). In this study, the daily feed intake and daily gain of piglets supplemented with SCE did not differ from those of the control group, even though SCE contains more crude protein and fat, which indicated that SCE did not affect the appetite and growth rate of piglets after weaning.…”
Section: Discussionmentioning
confidence: 51%
“…Pigs have received special attention in terms of characterization of the gut bacterial resistome, with recent studies demonstrating differential expression in humans, chickens, and specifically pigs [ 158 ]. Yet in chickens, the investigation into the ARGs associated with the gut microbiome has shown that the predominant classes are largely the same as those detected in pigs, including tetracycline, aminoglycoside and macrolide–lincosamide–streptogramin [ 159 ]. Of particular interest and utmost topicality is the risk of the potential transmission of ARGs from poultry meat to humans [ 160 ].…”
Section: Resistomementioning
confidence: 99%
“…1 However, the increasing spread of marker genes encoding antibiotic resistance and contamination with drug residues are both potential hazards to human health and the environment. 2,3 Antibiotics have been prohibited in the feed of livestock; however, this prohibition resulted in increased disease incidence in intensive poultry production and decreased the efficiency of animal feeding. 4,5 Therefore, there is an urgent need to develop natural substances as antibiotic alternatives.…”
Section: Introductionmentioning
confidence: 99%
“…For decades, subtherapeutic doses of antibiotic growth promoters have been used to improve the growth rate and feed conversion efficiency of poultry and prevent diseases that occur in intensive farming 1 . However, the increasing spread of marker genes encoding antibiotic resistance and contamination with drug residues are both potential hazards to human health and the environment 2,3 . Antibiotics have been prohibited in the feed of livestock; however, this prohibition resulted in increased disease incidence in intensive poultry production and decreased the efficiency of animal feeding 4,5 .…”
Section: Introductionmentioning
confidence: 99%